Young people in social networks: scaling social interactions and practices of forming individual media environments (based on regional studies) - Dmitrii V. Zernov; Nadezhda V. Shalyutina (Социологическая наука и социальная практика)
The relevance of young people’s digital practices in social networks learning is connected both with the growing influence of social media on all spheres of young people’s life and with the processes of adaptation of digital technology users to their own needs. Students’ use of social media is considered as a communicative practice influenced by objective and subjective factors. The users act as active persons, undertaking actions to combine communication channels based on the one hand, upon the socio-technical affords of social media and on the other hand, on their own goals and needs. The empirical basis of the analysis is the data of sociological research conducted among the student youth of Nizhny Novgorod from 2021 to 2023, including four questionnaire surveys (2021–2023) and one series of in-depth interviews (2023). Triangulation of the data from questionnaire surveys and materials of in-depth interviews of students allows describing media use practices both in quantitative data and in terms of social interactions meanings. The obtained data allow to identify the main elements that shape the practices of media using: 1) the choice of digital space of interactions (according to the parameters of publicity-privacy) and the practice of individual combination of social networks and messengers; 2) the number of accounts used; 3) user control over the personal information posted in the profile. Objective factors influencing young people’s choice of digital space are described through analysing the dynamics of social network popularity. It is concluded that the trend towards privacy of social interactions in the digital space is increasing. The paper outlines the scenarios of constructing an individual polymedia environment based on sociotechnical parameters corresponding to user motives and needs. Three main communication needs satisfied in social media are consi de red: 1) informal communication along the lines of “strong ties”, realised mainly through messengers; 2) maintaining “weak ties” by combining different media channels and managing the number of participants in interactions; 3) forming “quasi-connections” and observing “others”. It is shown that fulfilling these needs motivates young people to adapt their digital practices to different frames of social interactions, marking demarcations between public and private spaces. Two dominant strategies for shaping individual media environments are identified. It is concluded that young people scale their digital interactions based on a system of social expectations, needs and goals.